como determinar o mmc de : x²-4;2x+4;3x+6
iggyendres:
sim hehe .-.
Soluções para a tarefa
Respondido por
0
x²-4 -->( x+2)(x-2)
2x+4--> 2(x+2)
3x+6-->3(x+2)
mmc:
6(x+2)(x-2)
acho q está certo
espero ter ajudado :)
2x+4--> 2(x+2)
3x+6-->3(x+2)
mmc:
6(x+2)(x-2)
acho q está certo
espero ter ajudado :)
Respondido por
0
x²-4 ( x+2)(x-2)
2x+42(x+2)
3x+63(x+2)
----------------------------------------------------------------------------------------------------
6(x+2)(x-2)
2x+42(x+2)
3x+63(x+2)
----------------------------------------------------------------------------------------------------
6(x+2)(x-2)
Perguntas interessantes
Artes,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás